Penerapan simple multi attribute rating technique exploiting ranks method dalam pemilihan jenis tanaman pangan di Desa Bandar Kwala - Dewi, Sartika; Cipta, Hendra; Dur, Sajaratud (Jurusan Matematika FMIPA Universitas Jember, 2023)
In the field of agriculture in Indonesia, there are forms or types of plants, one of which is food crops. Currently, the food crops that develop in Bandar Kwala village are rice, corn, peanuts, and cassava. So that there is competition for nutrient absorption between plants and many types of plant-disturbing organisms that appear and cause farmers to experience crop failure, the selling price in the market is not proportional to the price of the seeds they buy and the care they do. For each type of plant that is planted, it is necessary to pay attention to the factors that affect the growth of a plant, one of which is land management, seeding, fertilization and pest control. The purpose of this research is to apply the SMARTER method to get the ranking of plants suitable for planting on agricultural land in Bandar Kwala village based on food crop criteria. In the SMARTER method, the ranking results are obtained by looking at the final value obtained by each alternative, where the alternative rice plant gets a final value of 0.9581 as the first rank, the cassava plants alternative gets a final value of 0.2628 as the second rank, the alternative to peanut plant gets the final score was 0.2354 as the third rank, and the alternative maize crop obtained a final score of 0.0899 as the fourth rank.Keywords: Plant, decision, rank, SMARTER MSC2020: 90B50